Blind Testing: DNA Barcoding Sheds Light Upon the Identity of Plant Fragments as a Subsidy for Cave Conservation - Ramalho, Aline J.; Zappi, Daniela C.; Nunes, Gisele L.; Watanabe, Mauricio T. C.; Vasconcelos, Santelmo; Dias, Mariana C.; Jaffé, Rodolfo; Prous, Xavier; Giannini, Tereza C.; Oliveira, Guilherme; Giulietti, Ana M. (Frontiers in Plant Science, 2018)
Plants living above and around caves represent an important, albeit poorly studied, resource within cave ecosystems. The presence of plant material (root-like structures or rhizothemes, saplings, seeds, seedlings) correlates positively with the biodiversity of the cave dwelling animals as shown for iron-ore caves in Carajás, Pará, Brazil. Plant material collected in caves has proven to be difficult to identify by traditional botanical methods, thus this research aims to provide a qualitative insight into the taxonomy and morphology of rhizothemes and other plant fragments found in the caves. The identification process used a combination of different molecular markers (ITS2, rbcL and trnH-psbA) followed by a comparison of the sequences obtained against publicly available databases. The rhizothemes were submitted to micromorphological analysis to ascertain their putative root or stem origin and to compare their anatomy with known patterns found in the plant families or genera recovered through molecular matches. All studied samples were Angiosperms, mostly belonging to subclass Rosideae, within four orders: Malpighiales (Euphorbiaceae, Hypericaceae), Sapindales (Anacardiaceae and Sapindaceae), Myrtales (Myrtaceae), Fabales (Fabaceae), and only two belonging to subclass Asteridae, order Gentianales (Apocynaceae). Some of the samples were matched to generic level, with ITS2 being the best marker to identify the fragments because it shows high degree of sequence variation even at specific level and result reliability. All rhizothemes turned out to be roots, and correspondence was found between the existing literature and the individual anatomical patterns for the families and genera retrieved. DNA barcode has proved to be a useful tool to identify plant fragments found in this challenging environment. However, the existence of well curated, authoritatively named collections with ample biological information has proven to be essential to achieve a reliable identification.